1972
DOI: 10.1128/aac.1.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Immune and Hemopoietic Cellular Responses by Methisazone

Abstract: The antiviral drug methisazone (N-methylisatin ,B-thiosemicarbazone) was tested for its effect on immune responses to sheep erythrocytes and on hemopoietic colony-forming cell (granulocyte-macrophage progenitor cell) responses to complete Freund's adjuvant in mice. Suppressive activity was demonstrated in both systems, the immune system being more readily and more consistently susceptible. Evidence is presented which suggests that the insoluble particulate form of the drug has both stimulatory and suppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The present observations confirm for methisazone and extend to other related and more active compounds the finding of an inhibitory effect restricted to the early phase of the differentiation pathway. The implications in terms of antileukemia or immunosuppressive therapy have been previously referred to (6,7). The present observations on mouse marrow extend the range of possible agents available for such investigations, and the preliminary work with human VOL.…”
mentioning
confidence: 60%
“…The present observations confirm for methisazone and extend to other related and more active compounds the finding of an inhibitory effect restricted to the early phase of the differentiation pathway. The implications in terms of antileukemia or immunosuppressive therapy have been previously referred to (6,7). The present observations on mouse marrow extend the range of possible agents available for such investigations, and the preliminary work with human VOL.…”
mentioning
confidence: 60%
“…8). McNEILL et al (1972) found that the number of IgM-producing lymphocytes was reduced almost 5-fold compared with the number found in drug-free mice. There was almost a 20-fold difference when the number of IgG-producing cells was determined.…”
Section: Isatin-p-thiosemicarbazonesmentioning
confidence: 87%
“…The initial quantitative studies on the ability of thiosemicarbazones to inhibit the immune response in mice were carried out by McNEILL (1972McNEILL ( , 1973 and McNEILL et al (1972). The humoral response to sheep red blood cells (see Sect.…”
Section: Isatin-p-thiosemicarbazonesmentioning
confidence: 99%
See 2 more Smart Citations